La mousson, pluie des agriculteurs et vent des marins - Françoise Aubaile-Sallenave (Revue d'ethnoécologie)
The monsoon is an arabic word (with its proper origin and history), which designates as well as winds, as marine streams, which go from indian Ocean to the china and japanese sea. That large zone of intense movements putt in contacts very diverse populations.The monsoon facilitated since a very long time the travels from east to west (China to India and persian gulf) and from west to east (South Arabia to Indonesia and China), travels which gave access to the islands and peninsulas of India and southeast Asia, rich in spices and fine products. But monsoon obliges the travelers to accomodate to its very particular annual calendars : it directs the boats alternatively from west to east and from east to west.The cultural frame of the paper focalizes the arabo-muslim world of the 8th-16th, 18th centuries, with glimpses on the other cultures (in term of boats, travels, travelers, products).We shall evocate the action of the monsoon on the land and the adaptation of the small farmers to those rains, but also the good and bad consequences of those rains for the societies.We also shall evocate the steps of the trade (chinese, indian, arabic, persian, then portuguese, english and french), some great oriental and occidental travelers, their aims.For the Europeans in the Indian Ocean, that monsoon route has been first the alternative to the inside asiatic route, the silk route. But overall, the monsoon route merges into the discovery of the world. That large zone, linked to the search of the spices, is the starting point of great explorations, and world tours, therefore of the world conquest.